ANALISIS KOMPARATIF PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DALAM SUSTAINABILITY REPORT PT BANK CENTRAL ASIA TBK DAN PT BANK NEGARA INDONESIA (PERSERO) TBK BERDASARKAN GLOBAL REPORTING INITIATIVE G4 (Studi Kasus pada Sustainability Report PT Bank Central Asia Tbk dan PT Bank Negara Indonesia (Persero) Tbk tahun 2016) - Irma Surya Frany (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study is aimed to understand the Corporate Social Responsibility disclosure in theSustainability Reports of PT Bank Central Asia Tbk and PT Bank Negara Indonesia (Persero)Tbk, and to determine whether the disclosures are in accordance with GRI G4. The research alsocompared the Sustainability Reports of the two companies to find out which Sustainability Reporthad a higher suitability with GRI G4. This study combines two analytical techniques, namelycontent analysis and comparative analysis, to interpret and compare the contents of thesustainability reports of the two companies. The analysis in this study focuses on the fulfillmentof the Disclosure on Management Approach (DMA) and Indicators in three categories ofdisclosures: Economics (EC), Environment (EN), and Social Affairs consisting of the subcategories of Labor and Work Comfort Practices (LA), Human Rights (HR), Society (SO), andProduct Responsibility (PR). The data collection technique used in this study is document study.From the results of the interpretation and comparison of sustainability reports, it was found thatPT. Bank Central Asia Tbk had a total disclosure percentage of material aspects which wereidentified for DMA to 75.07% and for Indicators to 48.13%, and thus the total average percentageof material aspects obtained for all disclosure categories is 61.60%. Meanwhile, PT. Bank NegaraIndonesia (Persero) Tbk had a total percentage disclosure of material aspects identified for DMAto 86.01% and for Indicators to 57.85%, and so the total average percentage of disclosure ofmaterial aspects obtained for all categories of disclosure amounted to 71.93%. This studyindicates that the disclosure of Corporate Social Responsibility in the Sustainability Report ofPT Bank Negara Indonesia (Persero) Tbk is higher in conformity with GRI G4 compared to PTBank Central Asia Tbk.Keywords: Corporate Social Responsibility, Sustainability Report, GRI G4, DMA, Indicator,PT Bank Central Asia Tbk, PT Bank Negara Indonesia (Persero) Tbk